MtCAS31 Aids Symbiotic Nitrogen Fixation by Protecting the Leghemoglobin MtLb120-1 Under Drought Stress in Medicago truncatula - Li, Xin; Feng, Hao; Wen, JiangQi; Dong, Jiangli; Wang, Tao (Frontiers in Plant Science, 2018)
Symbiotic nitrogen fixation (SNF) in legume root nodules injects millions of tons of nitrogen into agricultural lands and provides ammonia to non-legume crops under N-deficient conditions. During plant growth and development, environmental stresses, such as drought, salt, cold and heat stress are unavoidable. This raises an interesting question as to how the legumes cope with the environmental stress along with SNF. Under drought stress, dehydrin proteins are accumulated, which function as protein protector and osmotic substances. In this study, we found that the dehydrin MtCAS31 (cold-acclimation-specific 31) functions in SNF in Medicago truncatula during drought stress. We found that MtCAS31 is expressed in nodules and interacts with leghemoglobin MtLb120-1. The interaction between the two proteins protects MtLb120-1 from denaturation under thermal stress in vivo. Compared to wild-type plants, cas31 mutants display a lower nitrogenase activity, a lower ATP/ADP ratio, higher expression of nodule senescence genes and higher accumulation of amyloplasts under dehydration conditions. The results suggested that MtCAS31 protects MtLb120-1 from the damage of drought stress. We identified a new function for dehydrins in SNF under drought stress, which enriches the understanding of the molecular mechanism of dehydrins.